THE MEDIATING ROLE OF TRANSPARENCY IN THE IMPACT OF DIGITALIZATION ON TAX EVASION (Third Sector Social Economic Review, 2024)
This study aims to identify the impact of digitalization on tax evasion. The study also examines whether transparency mediates the impact of digitalization on tax evasion. In this context, the study, which includes data from 137 countries in 2016, is primarily tested with regression analysis. The findings show that the effect of digitalization on tax evasion is negative and strong. The study also conducted a analysis based on the PROCESS Model 4 to test whether transparency has a mediating role in the effect of digitalization on tax evasion and found that transparency has a mediating effect. As a result of these findings, it is thought that technological investments and structural transformations in the field of digitalization will foster transparency and this process will increase the deterrence of losses and evasion in taxation processes in the long run.
Keywords: Tax Evasion; Digitalization; Digitalization Adoption Index; Transparency; Mediating Effect